Apology and Its Acceptance: Perceived Reconciliatory Attitudes Reduce Outgroup Dehumanization - Jin, Wen Jie; Park, Sang Hee; Park, Joonha (Frontiers in Psychology, 2022)
Based on real-life intergroup animosities originating from a historical conflict, the current study examined how perceived stance of the outgroup about the conflict affects dehumanization of the outgroup. In Study 1 (N = 120), Korean undergraduates attributed less human nature to Japanese after reading an article that the Japanese government refused to (vs. did) issue an official apology for a historical wrong. In turn, the less human nature assigned to Japanese predicted lower expectations about positive mutual relations in the future. Similarly, in Study 2 (N = 209), Japanese undergraduates attributed less human uniqueness to Koreans after reading an article that an official apology for a historical wrong from Japan was rejected (vs. accepted) by Koreans. The lower perceived human uniqueness of Koreans in turn predicted less willingness to help and expectations of positive relationship in the future. The findings demonstrate how mutual dehumanization can occur as a result of the other side’s nonreconciliatory stances, and further exacerbate intergroup relations.